2013
DOI: 10.1038/srep01871
|View full text |Cite
|
Sign up to set email alerts
|

The strange flight behaviour of slowly spinning soccer balls

Abstract: The strange three-dimensional flight behaviour of slowly spinning soccer balls is one of the most interesting and unknown phenomenon associated with the trajectories of sports balls. Many spectators have experienced numerous exciting and emotional instances while observing the curious flight behaviour of these balls. We examine the aerodynamic mechanisms of erratic ball behaviours through real flight observations, unsteady force measurements and flow pattern visualisations. The strange behaviour is elucidated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 7 publications
2
13
0
1
Order By: Relevance
“…Our results also showed the same tendencies as those found in a prior study conducted on the four types of modern soccer balls (Jabulani, Teamgeist2, Tango12, and Roteiro)1. Preceding studies on drag characteristics of soccer balls reported that different types of soccer balls have different levels of aerodynamic forces91415. Based on these findings, we verified the validity of our measurement system.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results also showed the same tendencies as those found in a prior study conducted on the four types of modern soccer balls (Jabulani, Teamgeist2, Tango12, and Roteiro)1. Preceding studies on drag characteristics of soccer balls reported that different types of soccer balls have different levels of aerodynamic forces91415. Based on these findings, we verified the validity of our measurement system.…”
Section: Discussionsupporting
confidence: 88%
“…There have also been studies in recent years to examine the flight characteristics of soccer balls using both the wind tunnel and actual flight paths8910. Furthermore, there was a recent report on the effect of the surface geometry on the flight trajectory, which was determined by trajectory analysis and high-speed cameras11.…”
mentioning
confidence: 99%
“…One knows that the critical Reynolds number of the drag crisis strongly depends on the texture of the ball [24]. This effect occurs in a range of velocity between 15m s −1 and 25 m s −1 for soccer [25], between 16 m s −1 and 18 m s −1 for volleyball [6] and between 30 and 35m s −1 for baseball [16]. All these ranges of velocity are in good agreement with the ones where knuckleballs are observed [table 1]: increase of lateral deviations in the drag crisis regime appears to be essential to observe zigzag paths in sports.…”
Section: Conditions For Observationmentioning
confidence: 99%
“…The vortex pairs in the wake of the spinning ball (curve) tended to be stable, whereas those in the wake of the non-spinning or slowly spinning ball tended to be unstable, exhibiting large fluctuations such as rotation about the axis in the motion direction and breakdown. These instabilities are considered to be one of the causes of the knuckling effect observed in nonspinning and slowly spinning balls [17][18][19]. In addition, the deviation of side force coefficient of the spinning ball determined by CFD tended to be smaller than that of the non-spinning ball.…”
Section: Discussionmentioning
confidence: 99%